TYPOLOGI MASJID DIKOTA KENDARI DENGAN PENDEKATAN ARSITEKTUR ISLAM - Fitriani Fitriani; Arysandi Alex; La Pande Jurumai (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Kendari city is a city that has potential as a tourism and religious city area. Over time, the city of Kendari has produced many design works, such as mosques. Many types of mosques in the city of Kendari have implemented architectural designs. The mosque is not only for worship but also for Islamic activities and also for social activities. The purpose of this research is to identify the types of mosques in the city of Kendari and it is hoped that this research can add to our insights. The research method used is descriptive research method in which we survey directly to the field to see how Islamic architecture is applied to mosques in the city of Kendari. The results of the research obtained are that mosques in the city of Kendari have various forms and various ornaments and do not eliminate Islamic nuances.